1998
DOI: 10.3892/ijmm_00000028
|View full text |Cite
|
Sign up to set email alerts
|

UDP-GlcNAc2-epimerase regulates cell surface sialylation and ceramide-induced cell death in human malignant lymphoma

Abstract: Abstract. Stress signals induce ceramide (cer) through sphingomyelinase activation, and metabolites of cer such as sphingosine (Sph) and sphingosine-1-phoshate (S-1-P) play a significant role in many biological processes. This study aimed to elucidate the association between the alteration in cell surface sialylation and ceramide-induced cell death in the human Burkitt's lymphoma cell line, HBL-8. The highly sialylated 3G3 clone was less sensitive to C6-ceramideinduced cell death. On the other hand, the hyposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…In addition, Morris hepatoma cell lines were reported with decreased GNE expression [60], as did a chicken hepatoma cell line [132], although no direct links to GNE promoter methylation status were reported for these lines. Human Burkitt's lymphoma cell lines demonstrated sensitivity to ceramide-induced cell death regulated by GNE expression levels [133]. Hyposialylation due to GNE down-regulation was demonstrated in at least two non-cancerous cell lines.…”
Section: Gne-opathiesmentioning
confidence: 99%
“…In addition, Morris hepatoma cell lines were reported with decreased GNE expression [60], as did a chicken hepatoma cell line [132], although no direct links to GNE promoter methylation status were reported for these lines. Human Burkitt's lymphoma cell lines demonstrated sensitivity to ceramide-induced cell death regulated by GNE expression levels [133]. Hyposialylation due to GNE down-regulation was demonstrated in at least two non-cancerous cell lines.…”
Section: Gne-opathiesmentioning
confidence: 99%
“…. Stress within the vessels may induce the apoptosis of lymphoma cells, whereas sialylation is known to protect lymphoma cells from stress signals and may rescue lymphoma cells from apoptosis. We speculate that sialylation of cell surface glycoproteins may regulate cell adhesion in lymphoma, and desialylation by neuraminidase or knockdown of ST6Gal1 may enhance cell adhesion to galectin or extracellular matrix, thereby inhibiting the invasiveness or metastasis of lymphoma cells and providing a potential strategy for lymphoma glycotherapy by desialylation.…”
Section: Sialylation In the Adhesion And Invasion Of Lymphoma Cellsmentioning
confidence: 99%
“…. Knockdown of GNE in HBL‐8 3G3 cells appears to inhibit cell growth and enhance cell death caused by ceramide, an inducer of apoptosis or cell death . The survival of tumor cells from stress such as hypoxia, oxidative stress, or apoptosis may be related to increased metastatic tumors, and thus the high survival rate of 3G3 clone cells following sialylation may be associated with high metastasis in a SCID animal model.…”
Section: Modulated Adhesion or Oncolysis By Desialylation In Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, clone 3G3 was less sensitive to Sph than the 3D2 clone. In conclusion, in human malignant lymphoma, Cer and its metabolitesinduced cell death is regulated by the amount of sialic acid on the cell surface, which in turn is regulated by mRNA expression of UDP -GlcNAc2 -epimerase 67) . Goni et al recently reported that Cer and sphingolipids modified the physical properties of the cell membrane 68) , and Montes et al reported that Cer induced an increased efflux or permeability in cell membranes 69) .…”
Section: Sialylation and Cell Deathmentioning
confidence: 99%